PHOTOGRAPHICAL IMAGES OF THE LOST BERLIN COPY OF CHYLINSKIS’ OLD TESTAMENT RECOVERED - KAVALIŪNAITĖ, GINA (Knygotyra, 2015)
The article briefly outlines the circumstances of the printing of Chylinskis’ Bible and of its discontinuation. Chylinskis’ Lithuanian bible translation was the first to be at least partly published in print. His undertaking enjoyed the support of the most enlightened European minds of his day, as well as of King Charles II of England. The article gives an overview of the 17th and 18th century publications testifying to the renown of this bible. Numerous European bibliographies mention it probably without their authors having seen it. The circumstances of the discovery, in the 19th century, of the three known copies, including the only now extant copy, that of the British Library, are described. The known copies were of unequal size: the Vilnius copy had 416 pp. and ended with Psalm 40; the Berlin copy had 384 pp. and ended with Job 6; the London copy, the smallest, has 176 pp. and ends with Joshua 16. During the preparations for a facsimile edition of the only extant copy of Chylinskis’s bible, a complete, qualitatively satisfying photographical reproduction of the Berlin copy was discovered in the Manuscript Department of Vilnius University Library. For Lithuanian cultural history this is an important discovery, as the 200 pages with which the text known from the London copy is now being supplemented had never been published and was, until recently, thought to be lost forever.